Developments in International Bridge Engineering Selected Papers from Istanbul Bridge Conference 2014 - Caner, Alp; Gülkan, Polat; Mahmoud, Khaled (Springer Tracts on Transportation and Traffic,, 2016)
The book includes peer-reviewed contributions selected from presentations given at the Istanbul Bridge Conference 2014, held from August 11 - 13 in Istanbul, Turkey. It reports on the current challenges in bridge engineering faced by professionals around the globe, giving a special emphasis to recently developed techniques, innovations and opportunities. The book covers key topics in the field, including modeling and analysis methods; construction and erection techniques; design for extreme events and condition assessment and structural health monitoring. There is a balanced presentation of theory, research and practice. This book, which provides the readers with a comprehensive and timely reference guide on current practices in bridge engineering, is intended for professionals, academic researchers and students alike.